Crisis, learning and firm governance - Cucculelli, Marco (Piccola Impresa / Small Business, 2017)
This paper investigates the ability of the firm to learn from previous negative events – crisis – and to adapt its behaviour to new market conditions. Identification is provided by the changes of company CEO occurred in the time interval between the 2003 and 2009. Using a large dataset of firms that underwent a CEO change in the between–crisis period, empirical results show that the occurrence of learning from large crises is relatively limited. However, when observed, learning significantly influences the firm’s ability to reorganize and its financial performance.